Tailored bioprocessing of brewers’ spent grain for the development of upcycled plant-based spoonable snacks - Kamaljit Moirangthem; Antti Knaapila; Youngsun Lee; Mari Sandell; Iwona Skibinska; Kieran N. Kilcawley; Paula M. O'Connor; Henry N. Maina; Katariina Niklander; Emily P. Verhulst; Dilip K. Rai; Rossana Coda (Future Foods)
Reintegration of brewers' spent grain (BSG) into the food system remains a challenge. In this study, BSG underwent enzyme hydrolysis with Ondea Pro, followed by fermentation with Lactiplantibacillus plantarum POM1 or Pediococcus claussenii DSM 14800. Both bacterial strains exhausted C6 sugars and lowered the pH to below 4. This bioprocessing approach increased the total polyphenol, antioxidant capacity, and free amino acid content in a strain-dependent manner. Enzyme hydrolysis contributed to an increase in low molecular weight dietary fibre content, while fermentation reduced the abundance of volatile organic compounds with off-flavours such as malty, grassy and pungent, and increased fruity, citrus, sour and sweet aroma compounds. Unprocessed (control) and bioprocessed BSG were then used as ingredients for semi-solid -spoonable snack prototypes with or without strawberry purée. A consumer sensory study involving 119 untrained participants showed higher liking for unprocessed samples, likely due to the bitter taste of the bioprocessed samples. However, adding purée increased the liking in all cases, while only fermentation could enhance the presumably desired aroma notes and reduce the presumably undesired cereal aroma and flavour. These findings suggested that tailored bioprocessing, informed by sensory data, could support the development of functional upcycled food with a cleaner ingredients label.